2016
DOI: 10.1155/2016/5045248
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells in Systemic Lupus Erythematosus: From Pathogenic Players to Therapeutic Tools

Abstract: System lupus erythematosus (SLE) is a multifactorial systemic autoimmune disease with a wide variety of presenting features. SLE is believed to result from dysregulated immune responses, loss of tolerance of CD4 T cells and B cells to ubiquitous self-antigens, and the subsequent production of anti-nuclear and other autoreactive antibodies. Recent research has associated lupus development with changes in the dendritic cell (DC) compartment, including altered DC subset frequency and localization, overactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 143 publications
(131 reference statements)
3
30
1
Order By: Relevance
“…The role of pDCs in cancer is supported by the observation of pDC restoration in peripheral blood in patients under anticancer treatment . In contrast to pDC associated conditions such as primary Sjögren's syndrome and systemic sclerosis that show accumulation of pDCs at the side of inflammation , we observed a moderate decrease in the estimated pDC numbers in biopsies. Here, it is important to consider that it was previously found that pDCs in mice can be segregated into multiple populations with functional differences.…”
Section: Discussionsupporting
confidence: 56%
“…The role of pDCs in cancer is supported by the observation of pDC restoration in peripheral blood in patients under anticancer treatment . In contrast to pDC associated conditions such as primary Sjögren's syndrome and systemic sclerosis that show accumulation of pDCs at the side of inflammation , we observed a moderate decrease in the estimated pDC numbers in biopsies. Here, it is important to consider that it was previously found that pDCs in mice can be segregated into multiple populations with functional differences.…”
Section: Discussionsupporting
confidence: 56%
“…These findings were largely consistent in both cohorts and are in keeping with previous studies (21–23). The cytokines IP10, sCD40L and TNFα are important mediators of B and T lymphocyte activation, inflammation and autoantibody production in SLE and the consistent elevation of these cytokines is likely a reflection of the central importance of these immune processes in SLE pathogenesis (24). Similarly, VEGF is of paramount importance in the development of vascular pathology in SLE patients and is a useful biomarker for detecting systemic involvement in these patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…26 In SLE patients the DC population has well-established abnormalities thus there is an increased population of plasmacytoid DC (pDC), which produce type 1 INF in response to nucleic acid via TLR7 and TLR 9 activation, a reduced conventional DC population which, in SLE, promote autoreactivity instead of self-tolerance. 27 The complement system also participates in SLE. 28 Complement consumption is one of the markers for SLE activity as inflammation leads to complement system activation and, among other functions, opsonization of IC.…”
Section: Sle Immunobiologymentioning
confidence: 99%